Structural Characterization and Bioactivity Evaluation of Selenium-Modified Dihydromyricetin from Vine Tea - Kaixuan Cheng; Guangqian Hou; Shengqi Mei; Xingxing Gao; Chi Zhang; Longchen Shang; Shuai Chen (Foods)
Dihydromyricetin, the predominant bioactive constituent in vine tea, manifests diverse bioactivities, including anti-tumoral and anti-inflammatory effects. However, the deep processing of vine tea remains underdeveloped, thereby curtailing its economic benefits. Concurrently, as the demand for organic selenium products escalates, the exploration and development of selenium-containing compounds bearing synergistic effects has emerged as a research frontier. In this investigation, dihydromyricetin underwent selenium modification through a SeO2- and HCl-catalyzed reaction, leading to the successful synthesis of selenium-modified dihydromyricetin. A comprehensive array of characterization techniques—encompassing Fourier-transform infrared spectroscopy and solid-state nuclear magnetic resonance—was employed for structural elucidation. The results demonstrated that selenium was covalently tethered to the 4’-hydroxyl group of the B-ring of dihydromyricetin via an O-Se-O bond. Activity assays revealed that selenium-modified dihydromyricetin exhibited significantly augmented inhibitory effects on α-amylase and α-glucosidase (p < 0.05) relative to dihydromyricetin, with IC50 values of 0.0459 mg/mL and 0.01728 mg/mL, respectively. Moreover, selenium-modified dihydromyricetin exerted marked inhibitory effects on the proliferation of HepG2 and A549 cells, with IC50 values of 49.05 μg/mL and 515.60 μg/mL, respectively. These findings collectively furnish experimental evidence underpinning the potential application of selenium-modified dihydromyricetin as a functional food ingredient, particularly within blood glucose regulation.